Thermodynamics of Bi2O3-SiO2 System - Onderka, Boguslaw Zbigniew; Fitzner, Krzysztof; Kopyto, Marek; Przybylo, Witold (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Thermodynamic properties of the liquid Bi2O3-SiO2 solutions were derived from the results of the electrochemical studies by use of the solid oxide galvanic cells with YSZ electrolyte. Activities of Bi2O3 in silicate melts were determined directly in the temperature range from 1073 to 1293 K and for SiO2 mole fractions 0.2, 0.3, 0.4, and 0.5 from measured e.m.f.’s (electromotive force) of the cell: Bi, Bi2O3-SiO2 | YSZ | air (pO2 = 0.213 bar) Additionally, heat capacity data obtained for two solid phases 6Bi2O3·SiO2 and 2Bi2O3·3SiO2 were included into optimization of thermodynamic properties of the system. Optimization procedure was supported by differential thermal analysis (DTA) data obtained in this work as well as those accepted from the literature. Using the data obtained in this work, and the information about phase equilibria found in the literature, binary system Bi2O3-SiO2 was assessed with the ThermoCalc software.